Grain productivity of four maize three-way hybrids with andro-esterile and fertile versions. - Tadeo-Robledo, Margarita; Espinosa-Calderón, Alejandro; Turrent-Fernández, Antonio; Zamudio-González, Benjamín; Valdivia-Bernal, Roberto; Andrés-Meza, Pablo (Agronomía Mesoamericana, 2014)
The objective of this study was to evaluate the productivity of maize hybrids developed for The High Valleys of Mexico. Four hybrids in their versions of male-sterile and fertile were evaluated in four uniform experiments using a randomized complete block design, at the Experimental Station of Mexico (CEVAMEX) and the Faculty of Higher Studios Cuautitlan (FESC-UNAM). The statistical analysis was performed in a combined form with the factors: hybrids (4), locations (4), male sterility/fertility versions (2), and the interactions between these factors. Significant differences for genotypes (p≤0.01), for locations and for interaction hybrid x locations (p≤0.05) were detected. The coefficient of variation for seed yield was 21.5% and overall mean was of 6,998 kg/ha. The site CEVAMEX 2009, in its first planting date, produced 8829 kg/ha and surpassed the other three environments. The performance of the four hybrids was similar (p>0.05). The male sterile version had a yield of 7170 kg/ha, similar (p>0.05) to the fertile version (6826 kg/ha), which confirms that the versions of the fertile and male-sterile hybrids of this study are isogenic.